THE CONCEPTION OF INTERNATIONAL PROTECTION TO STATELY REFUGEES IN THE LEGAL SCOPE OF THE BRAZILIAN STATE (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The work addresses the reflexes of the evolution of human rights directly with regard to stateless persons in Brazilian legislation, balancing themselves with internal policy and guarantees in constitutional agreement. Human rights seek to ensure that all people achieve the right to nationality. Thus, the method used was to review the literature in a timely manner to the proposed theme, making sure that the global institutes were reconciled with Brazilian legislation and the perspective of harmonization between the standards, in order to fill the existing legal gaps and ensure the dignity a these peoples.